Thermodynamics of Transfer Processes of Triclosan from Water to Some Organic Solvents with Different Hydrogen Bonding Capability - Delgado, Daniel R. (2011)
The thermodynamic functions Gibbs energy, enthalpy and entropy for the dissolution and mixing processes of triclosan (TS) in water are presented. These quantities were calculated by using the van’t Hoff and Gibbs equations from solubility values determined in the temperature range from 293.15 to 313.15 K. In addition, the corresponding thermodynamic quantities of the drug transfer processes from water to some organic solvents with different hydrogen bonding capability were also calculated. In all cases, Gibbs energy of transfer comprised negative values, indicating the preference of TS for all the organic media evaluated. Nevertheless, enthalpy and entropy of transfer assumed positive or negative values according to specific system. It was clear that hydrogen bonding plays a significant role on dissolution and transfer processes.